Preliminary Studies on the Role of Trenches in Isolating Root Effect of Forest Trees Bordering Agricultural Crops - Singh, A; Daya, Rajbans (Annals of Arid Zone, 2016)
Technique ofÂ "Trenching" was studied for reducing the influence of trees on agricultural crops under farm forestry programme at Soil Conservation Research Farm, Vasad. Yield rif cotton and tobacco increased by 21 and 68% respectively when lateral tree roots were cut-off by digging a trench between two land-uses.